Gastric Projecting Neurons of Dorsal (Motor) Nucleus of the vagus nerve (DMV) and their arborization - Awan, Khalid Latif; Rutherford, John G. (Journal of Postgraduate Medical Institute, 2011)
The purpose of this study is to locate the gastric projecting neurons in the DMV and examine their dendritic arborization. To achieve these objectives aqueous solution of cholera toxin conjugated horseradish peroxidase (CT-HRP) was injected in the walls of the stomach using Hamilton syringe. The retrogradely labelled gastric projecting neurosons and their dendritic arborization was mapped in the DVC. Teh anterograde labeling was also observed int ehDMV and subnuclei of the nucleus f the tractus solitarius (NTS). This light microscopic study revelaed the areas where overlapping between the DMV, its dendritic tree and afferent terminals of the central nucleus of the amygdala (ceA) could occur. These areas will be taken up for future ultrasstructural evidence for synapses between the axon terminals of the CeA and gastric projecting neurons. In addition vago-vagal connections were observed.